Perioperative docetaxel, cisplatin, and 5-fluorouracil compared to standard chemotherapy for resectable gastroesophageal adenocarcinoma. Issue 1 (January 2017) - Kim, S.; Paget-Bailly, S.; Messager, M.; Nguyen, T.; Mathieu, P.; Lamfichekh, N.; Fein, F.; Fratté, S.; Cléau, D.; Lakkis, Z.; Jary, M.; Sakek, N.; et al.
Abstract: Background: Even though the perioperative chemotherapy improves the overall survival (OS) compared to surgery alone in patients with a resectable gastroesophageal adenocarcinoma (GEA), prognosis of these patients remains poor. Docetaxel (D), cisplatin (C), and 5-fluorouracil (F) regimen improves OS compared to CF among patients with advanced GEA. We evaluated the potential interest of a perioperative DCF regimen, compared to standard (S) regimens, in resectable GEA patients. Methods: We identified 459 patients treated with preoperative DCF or S regimens. The primary endpoint was OS. Propensity scores were estimated with a logistic regression model in which all baseline covariates were included. We then used two methods to take PS into account and thus make DCF and S patients comparable. OS analyses were performed with Kaplan–Meier and Cox models in propensity score matched samples, and inverse probability of treatment weighted (IPTW) samples. Results: In the propensity score matched sample, the p-value from the log rank test for OS was 0.0961, and the 3-year OS rate was 73% and 55% in DCF and S groups, respectively. The multivariate Cox regression underlined a Hazard Ratio of 0.55 (95% CI 0.27–1.13) for DCF patients compared to S patients. The results from IPTW analyses showed that DCF was significantly and independently associated with OS (HR = 0.52; 95% CI 0.40–0.69). Conclusions: In this retrospective multicenter, hypothesis-generating study, the propensity score analyses underlined encouraging results in favor of DCF compared to S regimens regarding OS. This promising result should be validated in a phase-3 trial.